2020
DOI: 10.21203/rs.3.rs-23805/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mobile Applications for COVID-19: A Scoping Review of the Initial Response in Canada

Abstract: Background: The rapid outbreak of Coronavirus diseases (COVID-19) originating in Wuhan, China, and the subsequent declaration of a state of “pandemic” on March 11, 2020 has necessitated a widespread global response to manage and control the transmission, spread and impact of COVID-19. Mobile technology has been leveraged in a number of ways to control the spread of COVID-19, including to support knowledge translation. Mobile applications are accessible, acceptable, easily adopted, and have the ability to suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Several studies have reported similar findings, and they suggested that the majority of apps were focused on contact tracing and were available on both Android and iOS platforms. 15,37,38,59 In addition, a few applications such as Mawid, Sehha, Aarogya Setu and PathCheck provided online consultations, facilitating the practice of social distancing and home quarantine procedures, and ensuring continuity in delivering healthcare services for various conditions/diseases. It should be noted that launching different apps for different services such as consultation, awareness (information), contact tracing and travel permits may confuse citizens and create ambiguity over the use of applications for COVID-19.…”
Section: Covid Watch Appmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have reported similar findings, and they suggested that the majority of apps were focused on contact tracing and were available on both Android and iOS platforms. 15,37,38,59 In addition, a few applications such as Mawid, Sehha, Aarogya Setu and PathCheck provided online consultations, facilitating the practice of social distancing and home quarantine procedures, and ensuring continuity in delivering healthcare services for various conditions/diseases. It should be noted that launching different apps for different services such as consultation, awareness (information), contact tracing and travel permits may confuse citizens and create ambiguity over the use of applications for COVID-19.…”
Section: Covid Watch Appmentioning
confidence: 99%
“…12 Consequently, various countries have developed mobile health applications to improve the delivery of healthcare services to contain the spread of the novel coronavirus during the COVID-19 pandemic. [13][14][15][16][17][18][19][20][21] It is pertinent to point out that in general several of these studies are related to the present investigation. For example, one study indicated that more than 2 million of participants used a free smartphone-based app to report potential symptoms of COVID-19 in the United Kingdom and the USA.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations